Differentiating Blood, Lymph, and Primo Vessels by Residual Time Characteristic of Fluorescent Nanoparticles in a Tumor Model. (9th April 2013) - Lee, Sungwoo; Lim, Jaekwan; Cha, Jinmyung; Lee, Jin-Kyu; Ryu, Yeon Hee; Kim, SungChul; Soh, Kwang-Sup
Abstract : Fluorescent nanoparticles (FNPs) which were injected into a tumor tissue flowed out through the blood and lymph vessels. The FNPs in blood vessels remained only in the order for few minutes while those in lymph vessels remained for a long time disappearing completely in 25 hours. We found a primo vessel inside a lymph vessel near a blood vessel, and FNPs remained in the primo vessel for longer than 25 hours. In addition, we examined in detail the residual time characteristics of lymph vessels because it could be useful in a future study of fluid dynamical comparison of the three conduits. These residual time characteristics of FNPs in the three kinds of vessels may have implications for the dynamics of nanoparticle drugs for cancer chemotherapy.